Quantitative Molecular Detection of 19 Major Pathogens in the Interdental Biofilm of Periodontally Healthy Young Adults - Carrouel, Florence; Viennot, Stéphane; Santamaria, Julie; Veber, Philippe; Bourgeois, Denis (Frontiers in Microbiology, 2016)
In oral health, the interdental spaces are a real ecological niche for which the body has few or no alternative defenses and where the traditional daily methods for control by disrupting biofilm are not adequate. The interdental spaces are the source of many hypotheses regarding their potential associations with and/or causes of cardiovascular disease, diabetes, chronic kidney disease, degenerative disease, and depression. This PCR study is the first to describe the interdental microbiota in healthy adults aged 18-35 yrs old with reference to the Socransky complexes. The complexes tended to reflect microbial succession events in developing dental biofilms. Early colonizers included members of the yellow, green and purple complexes. The orange complex bacteria generally appear after the early colonizers and include many putative periodontal pathogens, such as F. nucleatum. The red complex (P. gingivalis, T. forsythia and T. denticola) was considered the climax community and is on the list of putative periodontal pathogens. The 19 major periodontal pathogens tested were expressed at various levels. F. nucleatum was the most abundant species, and the least abundant were A. viscosus, P. gingivalis and A. actino. a. The genome counts for E. corrodens, C. concisus, C. rectus, T. denticola and T. forsythensis increased significantly with subject age. The study highlights the observation that bacteria from the yellow complex (Streptococcus spp., S. mitis), the green complex (E. corrodens, C. gracilis, C. ochracea, C. sputigena, A. actino a), the purple complex (V. parvula, A. ondotolitycus) and the blue complex (A. viscosus) are correlated. Concerning the orange complex, F. nucleatum is the most abundant species in interdental biofilm. The red complex, which is recognized as the most important pathogen in adult periodontal disease, represents 8.08% of the 19 bacteria analyzed. P. gingivalis was detected in 19% of healthy subjects and represents 0.02% of the interdental biofilm. T. forsythensis and T. denticola (0.02% and 0.04% of the interdental biofilm) were detected in 93% and 49% of healthy subjects, respectively. The effective presence of periodontal pathogens is a strong indicator of the need to develop new methods for disrupting interdental biofilm in daily oral hygiene.